2018
DOI: 10.1007/s00192-018-3650-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for anatomic pelvic organ prolapse at 6 weeks postpartum: a prospective observational study

Abstract: Prelabor differences in the pelvic floor rather than obstetrical events were risk factors for aPOP at 6 weeks postpartum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
(34 reference statements)
2
21
0
1
Order By: Relevance
“…Of the 19 studies on FI, including flatal incontinence, nine studies scored moderate for risk of bias and were included for data extraction (see Supporting information, Table ) 19,27,30,32,36,38,44‐46 and 10 studies were excluded because of high risk of bias. On the outcome POP, of the six included studies, four scored high risk of bias and two scored moderate risk of bias, indicating that two were eligible for data extraction (see Supporting information, Table ) 47,48 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 19 studies on FI, including flatal incontinence, nine studies scored moderate for risk of bias and were included for data extraction (see Supporting information, Table ) 19,27,30,32,36,38,44‐46 and 10 studies were excluded because of high risk of bias. On the outcome POP, of the six included studies, four scored high risk of bias and two scored moderate risk of bias, indicating that two were eligible for data extraction (see Supporting information, Table ) 47,48 …”
Section: Resultsmentioning
confidence: 99%
“…Only two eligible studies reported on risk factors for POP with a short‐term follow‐up period 47,48 . Cesarean section was the only risk factor that could be pooled (OR 0.39, 95% CI 0.14‐1.08).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations